2001
DOI: 10.1210/jcem.86.2.7225
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Melatonin Concentration before and during Testosterone Replacement in Klinefelter’s Syndrome: Relation to Hepatic Indolamine Metabolism and Sympathoadrenal Activity

Abstract: The mechanisms leading to alterations in plasma melatonin (MT) levels with testosterone replacement in Klinefelter's syndrome (KS) remain elusive. We investigated early morning plasma MT levels, urinary 6-sulfatoxymelatonin (6-SM) levels, and urinary catecholamine levels before and 6 months after testosterone treatment in 31 patients with KS and 20 healthy males to demonstrate whether alterations in plasma MT levels in such patients are due to subtle changes in sympathoadrenal activity and/or alterations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…A study in pineal melatonin deficient mice indicated that different immune cells and tissues were able to synthesise melatonin; thus, they could contribute to the detectable melatonin levels in these animals (28). In the present study, only daily melatonin concentrations were determined, as in other studies (24,29). Therefore, no information about the possible disturbances in the circadian melatonin rhythm was obtained, which was considered the main limitation of the study.…”
Section: Discussionmentioning
confidence: 71%
“…A study in pineal melatonin deficient mice indicated that different immune cells and tissues were able to synthesise melatonin; thus, they could contribute to the detectable melatonin levels in these animals (28). In the present study, only daily melatonin concentrations were determined, as in other studies (24,29). Therefore, no information about the possible disturbances in the circadian melatonin rhythm was obtained, which was considered the main limitation of the study.…”
Section: Discussionmentioning
confidence: 71%
“…Human studies indicate that decreased concentrations of circulating melatonin (such as those brought about by circadian disruption) can result in increased release of the gonadotropins luteinizing hormone and follicle-stimulating hormone from the pituitary and estrogen release by the ovaries (21)(22)(23)(24)(25). There is also evidence from clinical studies of a relationship between melatonin and male reproductive hormones (26)(27)(28)(29). Thus, through its control over gonadal hormone production, melatonin may have an inhibitory effect on hormone-dependent tumors.…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…17 The free testosterone can be determined by RIA method, 7,17 calculated from total testosterone and SHBG levels using a formula 18 or chemiluminescence method. 19 The formula for calculation of free testosterone level is free testoster- one (pmol/L) = total testosterone (nmol/L)/ (K x SHBG (nmol/L)+1) x 1000; K (1.6 x 10 9 L/mol) is the equilibrium constant of testosterone binding to SHBG. 18 Free testosterone level is considered better for clinical application as it is the active form.…”
Section: Discussionmentioning
confidence: 99%